DDoS Attack Mitigation using Distributed SDN Multi Controllers for Fog Based IoT Systems - Ramalakshmi , R.; Kavitha , D. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Software Defined Networking is an important platform today for handling huge like Internet of things and fog edge based networking devices. SDN is also a most prominent network platform for today’s industrial diversity of setup such as cloud data storage, Industrial Internet of Things (IIoT), Network Function Virtualization (NFV), and Security attacks. So, SDN is handling application layer resources and physical layer edge devices along with security protection. Resources like cloud database storage is not capable enough for handling today’s world huge data’s. Similarly, a huge data’s are originated from the various end devices via IoT based switches and gateways to the target resources. But due to the attacks like Denial of service (DoS) and Distributed denial of service attack (DDoS), the network is easily contaminated and destroyed the target resources and available bandwidth. So, in this scenario handling these data traffic and mitigating the attacks with privacy and authentication is an efficient task provided by SDN controller. But SDN controller will take only the managing and controlling part of the network. But still security is a very big concern in the today’s huge data collection from IoT and other smart devices. So, Fog computing framework plays a vital role today to reduce the DDoS attacks from the different edge data sources by creating a micro clouds or fog nodes before accessing the cloud resources to manage and mitigate the DDoS attacks with the help of Distributed SDN multi controller and provides the additional layer of security for the network. This paper proposed the Machine Learning (ML) based DDoS attack mitigation process in IoT based SDN environment with Fog computing approach and secures the network from malicious packets with good detection accuracy.